Subcellular localization of leptin and leptin receptor in breast cancer detected in an electron microscopic study - Abdulrazzaq, Saad Mohammed; Amjad, Nasser Muhammad; Al-Kubaisi, Muna Khaleel Dheyab; Mizan, Shaikh (Elsevier B.V., 2016)
Leptin (LEP) and leptin receptor (LEPR) have long been found associated with breast cancer. So far no high-resolution method such as electron microscopy has been used to investigate the subcellular localization of leptin and leptin receptor in breast cancer. We collected cancer and non-cancer breast tissues from 51 women with invasive ductal breast cancer. Leptin and leptin receptor in the tissues were estimated using immunohistochemistry (IHC). LEP and LEPR were localized at subcellular level by immunocytochemistry (ICC) using ultra-fine gold particle conjugated antibody, and visualized with transmission electron microscopy (TEM). IHC showed high presence of LEP and LEPR in 65% and 67% respectively of the breast cancer samples, 100% and 0% respectively of the adipose tissue samples, and no high presence in the non-cancer breast tissue samples. On TEM views both LEP and LEPR were found highly concentrated within the nucleus of the cancer cells, indicating that nucleus is the principal seat of action. However, presence of high concentration of LEP does not necessarily prove its over-expression, as often concluded, because LEP could be internalized from outside by LEPR in the cells. In contrast, LEPR is definitely over-expressed in the ductal breast cancer cells. Therefore, we hypothesize that over-expression of LEPR, rather than that of LEP has a fundamental role in breast carcinogenesis in particular, and probably for LEP-LEPR associated tumors in general.